Shared money, less conflict, stronger marriages: The relationship between money ownership perceptions, negative communication, financial satisfaction, marital satisfaction and marital instability - Boyle, Jeremy (Kansas State University, 2012)
The current study tests a conceptual model exploring the relationship between perceived money ownership (PMO) in marriage, negative communication, financial satisfaction, marital satisfaction and marital instability. Relying on a cross-sectional, convenience sample (N=345) of social media users, structural equation modeling was used to analyze the relationship between these variables. The results indicate that individuals who perceive money as shared in their relationship experience greater marital satisfaction and financial satisfaction and less marital instability, and that the relationship between PMO and these outcome variables are mediated by negative communication. Thus, having a shared money ownership perception is associated with lower levels of negative communication which in turn is associated with higher levels of financial satisfaction and marital satisfaction and lower levels of marital instability. These findings add to the literature on couples, finances, and relationships by showing that PMO is a potentially important variable in understanding relationship processes and outcomes in marriage.
Keywords: Money; Marriage; Finances; Ownership; Satisfaction; Psychology (0621)